What is the functional result of a delayed coloanal anastomosis in redo rectal surgery?. Issue 5 (9th April 2019) - Boullenois, Hortense; Lefevre, Jérémie H.; Creavin, Ben; Calmels, Mélanie; Voron, Thibault; Debove, Clotilde; Chafai, Najim; Parc, Yann
Abstract : Background: Delayed coloanal anastomosis (DCAA) may be used in patients with complex rectal conditions, such as chronic pelvic sepsis, low recto‐vaginal and recto‐vesical fistula; however, limited data are available. The aim is to report the morbidity and functional results of DCAA in redo rectal surgery. Methods: All patients undergoing DCAA between January 2014 and August 2017 were retrospectively included. Success was defined as a functional anastomosis without stoma, evaluated using the Low Anterior Resection Syndrome (LARS) score and the Gastrointestinal Quality of Life Index (GIQLI) functional assessment tools. Results: Of the 72 redo pelvic surgeries, 29 (40.3%) DCAA were performed over a 4‐year period. Indications for redo resection were chronic pelvic sepsis ( n  = 13, 44.8%), recto‐vaginal fistula ( n  = 11, 37.9%) and recto‐vesical fistula ( n  = 5, 17.2%). Mean interval period between the two procedures was 14 ± 3 days (8–21). Global major morbidity (Clavien‐Dindo III or IV) was seen in six patients (20.7%). Stoma closure was feasible for 22 (75.9%) patients after a median period of 78 days (interquartile range 61–98). The 6‐month success rate was 79.3%. Mean LARS was 28.8 ± 10.2 (3–41) (minor LARS) for 18 patients with no stoma at the end of follow‐up. LARS score was significantly better with a follow‐up >2 years (23.3 ± 12.2 versus 32.3 ± 7.9), P  = 0.074. Mean GIQLI score was 79.2 ± 14.3 (48–98). Conclusions: Transanal colonic pull through with delayed anastomosis for redo‐surgery in complex pelvic situations had low morbidity and avoided a permanent stoma in three out of four patients with an acceptable quality of life.